Evaluating liquid CO2 injection technique for oil recovery using core flood experiments - Hamdi, Z. (Society of Petroleum Engineers, 2016)
CO2 injection has been used for several decades as a successful recovery method in enhanced oil recovery. The main impact of CO2 is on lowering minimum miscibility pressure. However, the unfavorable mobility of CO2 force us to use CO2 with other methods such as water alternating gas to minimize this effect. Low temperature CO2 injection may cover the role of the water and other fluids in this process. The injection of CO2 at low temperatures open a unique opportunity to investigate the potential for usage of low temperature CO2 as an enhanced oil recovery method. In this study, the effect of low temperature injection in a high temperature system is evaluated. Earlier studies suggested that this method could be beneficial. However, it is not verified by core flooding experiments. If proven effective, the usage of CO2 would add its advantage along with its current huge economic and environmental advantages against other EOR methods. The results show that injection of low temperature CO2 has a direct impact on recovery factor inside a high temperature system. The main outcome of this study is the proof for the effectiveness of low temperature CO2 usage as early as a reliable secondary recovery method in macro scale without any major unfavorable effects such as early breakthrough and gravity override. This study provides an economic way to increase the recovery while minimum modifications of available techniques are needed. No chemical agents were used as the production cost should be minimized. In addition, this study provides the ability for CO2 storage which also favors other conventional methods in terms of CO2 emission. Â© 2016, Society of Petroleum Engineers.